Current and future gene therapies for hemoglobinopathies. Issue 3 (May 2020) - Brendel, Christian; Williams, David A.
Abstract : Purpose of review: In this work we briefly summarize the key features and currently available conventional therapies for the two main β-hemoglobinopathies, sickle cell disease (SCD) and β-thalassemia, and review the rapidly evolving field of novel and emerging genetic therapies to cure the disease. Recent findings: Gene therapy using viral vectors or designer nuclease-based gene editing is a relatively new field of medicine that uses the patient's own genetically modified cells to treat his or her own disease. Multiple different approaches are currently in development, and some have entered phase I clinical studies, including innovative therapies aiming at induction of fetal hemoglobin. Summary: Early short-term therapeutic benefit has been reported for some of the ongoing clinical trials, but confirmation of long-term safety and efficacy remains to be shown. Future therapies aiming at the targeted correction of specific disease-causing DNA mutations are emerging and will likely enter clinical testing in the near future.